Use of Visual Performance Feedback to Increase Teacher Use of Behavior-Specific Praise among High School Students with Severe Disabilities - Simmons, Michelle L.; Lock, Robin H.; Brendle, Janna; Sharp, Laurie A. (Journal of the American Academy of Special Education Professionals, 2020)
Behavior-specific praise has been deemed an effective, evidence-based positive behavioral intervention and support practice for use among high school students with severe intellectual disabilities. However, teachers are not adequately trained to use such practices with fidelity. One way to address this shortcoming is by implementing a performance feedback approach characterized with observations and consultations that provide visual performance feedback. Using a changing criterion research design, the present study evaluated the effect of a performance feedback approach to increase a high school teacher’s use of behavior-specific praise among students with severe disabilities. Results showed significant increases with the teacher-participant’s use of behavior-specific praise and mixed trends with the student-participants’ exhibition of challenging and replacement behaviors. A discussion of reported results was provided, along with implications for stakeholders in teacher preparation programs and high school contexts. Limitations and areas for future research were also addressed.